Survey dataset on workplace incivility, emotional exhaustion and adaptive performance among employees working in the front line: A case study - Nurdiyana Sumri; Daniella M. Mokhtar (Data in Brief, 2023)
The data belongs to a sample of 201 frontline workers in Malaysia. This demographic data was collected using a cross-sectional questionnaire via an online survey and analyzed using SPSS version 25. This data was used to investigate the relationship between workplace incivility, emotional exhaustion and adaptive performance (handling emergencies, handling work stress, creative problem solving, learning new tasks, technology and procedure and demonstrating interpersonal adaptability) among frontline workers. The analyzed data will be useful in contributing to further research into the effects of workplace incivility on employees’ well-being and job performance. It will also give insights to stakeholders and those at managerial level who formulate appropriate intervention plans to overcome or reduce the issue of workplace bullying among frontline workers.